ALLERGIC DISEASES AND METABOLIC SYNDROME: SOME ASPECTS OF THE COMBINED COURSE - V.D. Sakevych; V.I. Sakevych; T.A. Trybrat; S.V. Shut (Проблеми екології та медицини)
To study the features of the clinical course of allergic diseases in combination with abdominal obesity, which is associated with metabolic syndrome examined 45 patients with AS aged 19 to 65 years. Materials and methods. By age composition dominated by those aged 30 - 40 years (38%) (men accounted for 51% (23 patients), and women - 49% (22 patients)). At the time of the survey patients were in clinical remission stage and stopped receiving allergy medications 72 hours, the patients had severe comorbidity. The diagnosis is established based on diagnostic criteria ARIA (2008) (Allergic Rhinitis and its Impact on Asthma (ARIA) 2008 Update (in collaboration with the World Health Organization) for diagnostic algorithm adopted in Ukraine and approved by the Ministry of Health of Ukraine. On the basis of outpatient department four city clinic hospitals and allergy department of the Poltava Regional Hospital were held instrumental examination and inspection of allergy. Allergic survey conducted by the conventional method by setting skin prick-tests (LLC "Immunologist", Vinnitsa, Ukraine). Obesity - considered as a risk factor and component of metabolic syndrome. Anthropometric studies were performed by standard methods. Determined the: body weight, height, body mass index by the method Quetelet II. The degree of centralization zhyrovidkladennya assessed at a rate which is the ratio of the circumference of the waist size (OT) and hip circumference (OS). According to WHO recommendations, abdominal obesity is diagnosed in men in the index OT / OB more than 0.9, the women - more than 0.8. Results. Allergic diseases in 76% of cases are hereditary nature mainly by the mother (36%), mostly starts in childhood and teens (88%) and 44% is accompanied by other allergic diseases. In patients with AS in the structure of comorbidities SARS dominated (58%), including complicated broncho-pulmonary pathology (35%) and diseases of the gastrointestinal tract (44%). From the standpoint of assessment of individual risk of disease to the constitutional characteristic features of AS patients include overweight and centralization zhyrovidkladennya in male patients. Given the figures obtained depending on sex differences to note the importance of the constitutional component of the mechanisms of ventilation disorders in asthma and AR combined with abdominal obesity.